Application of international labour standards Application des normes internationales du travail = Applica cion des las normas internacionales del trabajo ; by country, conven tion and subject - International Labour Organisation ([s.l] : International Labour Organisation, 2011)
This CD contains the general report and individual comments from its 2010 report, pending observations from previous reports, and discussio ns of observations that were examined by the conference committee on th e application of standards at the International Labour Conference in 20 10.
Produced by the International Labour Standards Department based on d ocuments in the APPLIS and ILOLEX databases on International Labour Sta ndards.
The information on this CD is written in English, French and Spanish .
Keywords: Labor laws and legislation; CD-ROM.